Awareness, perceptions and practices regarding menstruation and menstrual hygiene among students of a college in Bengaluru Urban district, South India: a cross sectional study - Srinivasan, Deepa; Agrawal, Twinkle; Attokaran, Teny; Fathima, Farah Naaz; Johnson, Avita Rose (International Journal Of Community Medicine And Public Health, 2019)
Background: Millions of women face significant barriers in menstrual hygiene management due to inadequate awareness, misconceptions and erroneous practices. The objectives of the study were to assess the awareness, perceptions and practices regarding menstruation and their associated factors among youth of a peri-urban college in Bangalore Urban district. Methods: A cross-sectional study was conducted among both male and female students studying in a degree college. A pre-designed, face-validated structured questionnaire was administered to all students present on the day of the study. Results: Of the 758 students, 372 (49.1%) were male and 386 (50.9%) were female. The mean age was 19.35±1.40 years. A consolidated score above 50% i.e. 07/14 was considered adequate for knowledge. The mean knowledge score was 7.51±2.52. Overall 389 (51.3%) students had adequate knowledge. Awareness levels were significantly better among females (72.3%) than males (29.6%). Among the female students, 384 (99.5%) were aware of sanitary napkins, 165 (42.7%) of menstrual cup, 12 (3.1%) of tampon and 254 (65.8%) of reusable cloth, however majority (96.9%) preferred use of sanitary napkins. Among the female students, 42.6% were expected to follow some social and cultural restrictions during menstruation. Main source of information regarding menstruation and various menstrual products was internet. Misconceptions documented regarding menstruation included the belief that menstrual blood is poisonous (75.2%). Positive attitude towards menstruation was low both among male students (21.5%) and female students (48.4%). Conclusions: Awareness levels were poor among males than females. Practices regarding menstrual hygiene were adequate. However, misconceptions were widely prevalent among both genders indicating the need for health education among college-going childhood.